1996
DOI: 10.1002/(sici)1099-0496(199601)21:1<42::aid-ppul7>3.0.co;2-s
|View full text |Cite
|
Sign up to set email alerts
|

Lung mechanics in infants with left-to-right shunt congenital heart disease

Abstract: To clarify which hemodynamic measurement correlates best with lung mechanics in infants with congenital heart disease and left‐to‐right shunts, dynamic pulmonary function tests and echocardiography were performed in 26 infants with such disease (study infants) and in 37 normal, healthy infants (control infants). The tidal volume and pulmonary compliance (CL) were lower and airway resistance higher in infants with congenital heart disease than in control infants. A significant correlation was demonstrated betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
12
0
2

Year Published

2000
2000
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(20 citation statements)
references
References 24 publications
6
12
0
2
Order By: Relevance
“…Previous studies of infants with congenital heart disease have found similar changes (8)(9)(10). A study of infants with left-to-right shunt by Yau et al (11) found a reduction in compliance of the same magnitude as our study. The reduced compliance has been attributed to increased pulmonary blood flow and increased pulmonary artery pressure (8,11,12).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Previous studies of infants with congenital heart disease have found similar changes (8)(9)(10). A study of infants with left-to-right shunt by Yau et al (11) found a reduction in compliance of the same magnitude as our study. The reduced compliance has been attributed to increased pulmonary blood flow and increased pulmonary artery pressure (8,11,12).…”
Section: Discussionsupporting
confidence: 88%
“…A study of infants with left-to-right shunt by Yau et al (11) found a reduction in compliance of the same magnitude as our study. The reduced compliance has been attributed to increased pulmonary blood flow and increased pulmonary artery pressure (8,11,12). We had no measure of pulmonary artery pressure, but we found a relationship between an estimation of pulmonary blood flow and compliance of the respiratory system and between pulmonary vasculature markings and compliance of the respiratory system.…”
Section: Discussionsupporting
confidence: 87%
“…[23], CPB is responsible for an obstructive process in the bronchi, leading to bronchospasm and acidosis. Bronchospasm is also a frequent postoperative finding in patients with a large preoperative left to right shunt [28]. Thus, the use of HFOV to treat respiratory acidosis in an attempt to decrease PVR after CPB appears justified.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, preoperative pulmonary hyperperfusion may have a harmful impact on the small airways causing peripheral airway obstruction and alterations of the visco-elastic properties of the lung [18][19][20][21][22]. Nevertheless, Zaqout et al [10] found significantly better pulmonary outcome after percutaneous ASD-closure than after surgery.…”
Section: Discussionmentioning
confidence: 99%